2016
DOI: 10.1038/srep30540
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between up-regulation of cytochrome-c-oxidase and hemoglobin oxygenation induced by near-infrared laser

Abstract: Photobiomodulation, also known as low-level laser/light therapy (LLLT), refers to the use of red-to-near-infrared light to stimulate cellular functions for physiological or clinical benefits. The mechanism of LLLT is assumed to rely on photon absorption by cytochrome c oxidase (CCO), the terminal enzyme in the mitochondrial respiratory chain that catalyzes the reduction of oxygen for energy metabolism. In this study, we used broadband near-infrared spectroscopy (NIRS) to measure the LLLT-induced changes in CCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
162
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(177 citation statements)
references
References 43 publications
(84 reference statements)
5
162
0
Order By: Relevance
“…The main proposed mechanism for PBMT action is the absorption of photons at the electron transport chain complex IV, specifically by cytochrome c oxidase . The chronic effects of PBMT are related to increases in mitochondrial biogenesis and function, and it has been shown that LLLT stimulation increased mitochondrial mRNA expression and mitochondrial protein content .…”
Section: Introductionmentioning
confidence: 99%
“…The main proposed mechanism for PBMT action is the absorption of photons at the electron transport chain complex IV, specifically by cytochrome c oxidase . The chronic effects of PBMT are related to increases in mitochondrial biogenesis and function, and it has been shown that LLLT stimulation increased mitochondrial mRNA expression and mitochondrial protein content .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it was suggested that the infrared region of the spectrum could influence other chromospheres, despite the interaction by wavelengths higher than 900 nm, and particularly 1064 nm, with mitochondrial chromophores was not clearly demonstrated . Nevertheless, Wang et al demonstrated that 1064 nm laser light induces significant increases of cytochrome‐c‐oxidase concentration and that transcranial infrared laser stimulation causes upregulation of oxidized cytochrome‐c‐oxidase in the human brain. In addition, only few studies have investigated the 1064 nm Nd:YAG laser light photobiostimulatory effects .…”
Section: Introductionmentioning
confidence: 99%
“…LLLT exerts various effects on cells. When light passes through the epidermis to be absorbed by chromophores or photoreceptors (principally mitochondrial cytochrome c oxidase [CCO]), cellular metabolic activity is affected . LLLT can stimulate the proliferation of skin fibroblasts, accelerating wound‐healing.…”
Section: Introductionmentioning
confidence: 99%